Konsep dan Perkembangan Manajemen Risiko Perusahaan - Djajadikerta Hamfri (Jurnal Manajemen Maranatha, 2004)
Corporate Risk management is a scientific approach to the problem of dealing with the risk faced by business. Risk management is broader than insurance management in that it deals with both insurable and uninsurable risks, and the choice of the appropriate techniques for dealing with them. The objective of corporate risk management is to make sure that losses from risks do not prevent management from seeking corporate goals.Key words: risk, risk management, risk identification, risk assessment, risk control